Sistem Informasi Penjualan Pada Toko Buku Jendela Dunia Berbasis Web - Safarina Binashrillah; Tiara Aulia; Sherly Rindayanti; Risqi Choirunnisa; Vita Ariska; Rian Abdul Aziz (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
In the current era of globalization, the development of science and technology has developed rapidly. Everything needed is done quickly and accurately. This can be realized by using technology to its full potential. With the development of information technology and software, this has made it possible for conventional transactions to be carried out electronically. The purpose of this research is to design a website-based sales information system related to the absence of support that can support communication between visitors and the window shop world. The result of this research is an application of a Web-Based Sales Information System at the Jendela Dunia Bookstore. This system is built with the PHP programming language and MySQL for thedatabase.Keywords: database, electronics, globalization, software, MySQL, PHP, website